Beyond the gender pay gap - Larraz, Beatriz; Pavía, Jose M.; Vila, Luis E. (Convergencia Revista de Ciencias Sociales; Núm. 81 (2019): Convergencia Revista de Ciencias Sociales núm. 81 septiembre-diciembre 2019, 2019)
Gender inequality, and in particular wage gender inequality, has been considered a political priority in many countries over the last decades, with the focus centered on reducing the so-called gender pay gap, i.e., looking for a mean-convergence. However, approaching gender averages does not imply fairer (total and gender) wage distributions. Using micro-data from a nationally representative sample of Spain’s working population (N=216,769), we decompose total wage inequality into females and males’ wage inequality ( within groups) and gender inequality ( between groups) and explore the extent to which these depend on those labor characteristics previously identified as determinants of the average differences between men and women (“gender pay gap”). For this dataset, the analyses show that gender wage inequality is higher than total wage inequality and both, total and gender wage inequalities, increase with a worker’s age and education attainment.